Gas exchange rates at different vapor pressure deficits and water relations of 'Pera' sweet orange plants with citrus variegated chlorosis (CVC) - Habermann, G.; Machado, E. C.; Rodrigues, J. D.; Medina, C. L. (Elsevier B.V., 2003)
Net photosynthesis (A) and transpiration rates (E), stomatal conductance (g), water use efficiency (WUE), intrinsic water use efficiency (IWUE) and internal leaf CO2 concentration (C) in response to different vapor pressure deficit (1.2 and 2.5 kPa) were investigated in 'Pera' sweet orange plants affected by citrus variegated chlorosis (CVC), a disease caused by Xylella fastidiosa. All plants were well watered and leaf water potential (Pw) was also measured by the psychrometric technique. Results showed that healthy plants responded to higher vapor pressure deficit (VPD), lowering its net photosynthesis and transpiration rates, and stomatal conductance. However, diseased plants presented no clear response to VPD, showing lower A, E and g for both VPDs studied and very similar values to these variables in healthy plants at the highest VPD. Internal leaf CO2 concentration also decreased for healthy plants when under the highest VPD, and surprisingly, the same pattern of response was found in plants with CVC. These results, the lower Psi(w) and higher WUE values for diseased plants, indicated that this disease may cause stomatal dysfunction and affect the water resistance through xylem vessels, which ultimately may play some role in photosynthetic metabolism. (C) 2003 Elsevier B.V. B.V. All rights reserved.
Keywords: Xylella fastidiosa; Citrus sinensis L. Osbeck; photosynthesis; stomata